2023
DOI: 10.1002/jez.2733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of larval thermal conditions on limb regeneration in a ladybird beetle, Cheilomenes sexmaculata

Abstract: In view of global environmental change, ecological factors especially temperature, affect development of the poikilotherms like insects. Since ladybirds are at risk of injury under mass‐rearing conditions, their ability to regenerate injured limbs is highly crucial for their survival. Therefore, the effect of limb regeneration in relation to temperature forms the basis of the present study. The immature stages of insects, being more vulnerable to the surrounding temperature, were considered to study the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Interestingly, the pupal duration in scraped treatment was similar to control. This difference from previous studies where maximum delay was reported in the pupal stage (Wang et al, 2015;Saxena et al, 2016;Michaud et al, 2020;Rai et al, 2023), can be attributed to the absence of blastemal cells for the initiation of regeneration and hence no regeneration occurred in pupa. While delay in the developmental duration of the fourth larval stage of the amputated treatment demonstrated the attempt to form the blastema via cellular proliferation, with no blastema in the larvae entering pupation there was no initiation of regeneration.…”
Section: Resultscontrasting
confidence: 96%
“…Interestingly, the pupal duration in scraped treatment was similar to control. This difference from previous studies where maximum delay was reported in the pupal stage (Wang et al, 2015;Saxena et al, 2016;Michaud et al, 2020;Rai et al, 2023), can be attributed to the absence of blastemal cells for the initiation of regeneration and hence no regeneration occurred in pupa. While delay in the developmental duration of the fourth larval stage of the amputated treatment demonstrated the attempt to form the blastema via cellular proliferation, with no blastema in the larvae entering pupation there was no initiation of regeneration.…”
Section: Resultscontrasting
confidence: 96%
“…However, the latter three instars showed an extension in their PD, which was not visible for first instar. Thus, regenerated adults exhibited an increase in their PADD either by extending their development duration at the stage of amputation or by extending their PD, eventually delaying their TDP (Dewes, 1973;Kunkel, 1977;Rai et al, 2023;Wang et al, 2015;. This might be ascribed to a stress response of the entire animal due to the trauma of amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on limb regeneration in ladybird beetles (Abdelwahab et al, 2018;Michaud, Nedved, et al, 2020;Wang et al, 2015;Wu, Ma, et al, 2019;Yang et al, 2016) have reported a few developmental and reproductive costs. Till now, regeneration studies on C. sexmaculata have reported the influence of limb regeneration on the adult reproductive fitness (Saxena et al, 2016) and the effect of thermal conditioning during limb regeneration (Rai et al, 2023). The comparative study by Michaud, Nedved, et al (2020) reported that broad geographic distribution, guild dominance, polyphagy and interspecific competitiveness are some characteristics of this species with high levels of regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation